Translanguaging as a political stance: implications for English language education - Wei, Li (ELT journal, 2022)
Abstract Following the multilingual trend in language education, translanguaging advocates active use of multiple languages and other meaning-making resources in a dynamic and integrated way in teaching and learning. When it comes to foreign language education, translanguaging advocates a view that the languages the learners already have should and can play a very positive role in learning additional languages. Moreover, the knowledge already acquired through the learners’ first and/or prior learned languages also plays an important role in foreign-language-medium education. This view is more than a pedagogic or theoretical perspective; it is a political stance, a decolonizing stance, that this article explores. It discusses the implications of the political naming of languages and critiques notions such as academic English.